Individual and Social Predictors of Prosocial Behavior among Chinese Adolescents in Hong Kong - Lai, Frank H. Y.; Siu, Andrew M. H.; Shek, Daniel T. L. (Frontiers in Pediatrics, 2015)
Based on the human ecological model, this study hypothesized that individual competence in empathy, prosocial moral reasoning, and social influence from parents, peers, and school are the key determinants of prosocial behavior among Chinese adolescents in Hong Kong. We recruited a sample of high school students who engaged in volunteering activities regularly (N = 580). They completed a self-administrated questionnaire designed to measure prosocial behavior and its hypothesized predictors using a number of standardized instruments. The results of multiple regression show that social influence factors, including peer, school, and parent influence, are strong predictors of helping intention and prosocial behavior, while individual competence factors like empathy and prosocial moral reasoning are not. Male participants had higher empathy scores and helping intention than females, perceived their parents as more helpful, and their schools as more supportive of prosocial behavior. However, the significant predictors of prosocial behavior and helping intention were similar across gender. The findings indicate that social influence is strongly linked to prosocial behavior. This implies that socialization and social support for prosocial norms and behavior can exert a powerful influence on the behavior of young people in a Chinese population.